Different scaling of linear models and deep learning in UKBiobank brain images versus machine-learning datasets - Marc-Andre Schulz (Nature Portfolio, 2020)
Schulz et al. systematically benchmark performance scaling with increasingly sophisticated prediction algorithms and with increasing sample size in reference machine-learning and biomedical datasets. Complicated nonlinear intervariable relationships remain largely inaccessible for predicting key phenotypes from typical brain scans.